Medical technology intervention in improving the quality of life among the type 2 diabetes mellitus patients - Doddaiah, Sunil Kumar; Shwetha, G.; Gopi, Arun; Murthy, M. R. Narayana; S. Bilimale, Anil; Anil, Deepak (International Journal Of Community Medicine And Public Health, 2021)
Background: Diabetes is a chronic disease characterized by high blood glucose with a disruption of fat and protein metabolism. Severe restrictions in diet, daily medications and other complications of diabetes can adversely affect an individual’s health related quality of life. The present study was conducted to assess the effect of educational intervention on quality of life (QOL) among the type 2 diabetes mellitus (T2DM) patients in Mysuru city. Methods: A quasi-experimental study was conducted from 1 November 2019 to 31 May 2020 among 138 diabetes patients at an urban health centre, Mysuru. Information regarding socio-demographic characteristics was collected using a pre-tested semi structured questionnaire. Assessment of QOL was done using the WHOQOL-BREF questionnaire. Data was analysed using SPSS version 23 (licensed to JSS AHER). Results: The overall mean score of pre-test QOL of the study participants was 81.72±8.57 and post-test mean score was 86.43±6.322. It was observed that 68 (49.27%) participants had good total QOL score and 70 (50.72%) had poor total QOL score. Among all the 3 groups, group A showed improvement in QOL when compared to other 2 groups with 52.2% in post-test. Conclusions: Improved QOL was seen in educational intervention using smartphone app when compared to other two groups (handouts and control group). QOL is one of the important factors among T2DM patients and it is important to take effective measures to improve it along with focusing on behavioural changes and health education.